2009
DOI: 10.1200/jco.2007.15.0466
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Trial CWS-91 for Localized Soft Tissue Sarcoma in Children, Adolescents, and Young Adults

Abstract: Improved risk stratification enabled decreased therapy intensity for selected patients without compromising survival. Intensified chemotherapy with EVAIA did not improve outcome of localized high-risk rhabdomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
139
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 31 publications
9
139
1
1
Order By: Relevance
“…Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children. Finally, specific chemotherapy for A‐RMS and E‐RMS is an independent prognostic value in our study and others 2, 6, 7, 8, 9, 11, 14, 15, 38, 39, 40, 41, 43, 44, 45, 46, 47. North American and European pediatric groups have identified several risk factors (favorable location, IRSG stage, IRSG group, and age) to define the clinical group and deliver a regimen adapted to the risk group.…”
Section: Discussionsupporting
confidence: 78%
“…Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children. Finally, specific chemotherapy for A‐RMS and E‐RMS is an independent prognostic value in our study and others 2, 6, 7, 8, 9, 11, 14, 15, 38, 39, 40, 41, 43, 44, 45, 46, 47. North American and European pediatric groups have identified several risk factors (favorable location, IRSG stage, IRSG group, and age) to define the clinical group and deliver a regimen adapted to the risk group.…”
Section: Discussionsupporting
confidence: 78%
“…No decrease in survival could be shown. The result from 1990 to 2010 was similar to those in the third and fourth intergroup Rhabdomyosarcoma Studies and our results were better than those in CWS‐91 16, 20. As expected, the prognosis was worse for patients with metastatic disease than for patients with localised disease.…”
Section: Discussionsupporting
confidence: 88%
“…The prognosis regarding sex, age, pathological subtype and size was in accordance with earlier studies 9, 16, 18. Just as the report by Dantonello et al 16 showed, the primary site category with the best prognosis was the orbit and the worst was the category called other sites.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations